A Comparative Analysis Of Simple Additive Methods Weighting With Preference Selection Index In The Selection Of The Best Sales - Rahmat Budianto; Dewi Suranti; Reno Supardi (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
PT. Tunas Dwipa Matra Branch of Putri Hijau is a company engaged in the sale of motorcycles by cash and credit which is located in North Bengkulu Regency, Bengkulu Province. PT. Tunas Dwipa Matra needs a decision support system that can correct the weaknesses of the current system, namely data collection and sales selection which is still manual, namely by using a book, as a result, selecting the best salesperson takes a very long time. In fact, for the assessment of the best sales selection, accuracy and precision are needed, so that the results can be accepted by all sales and employees at PT. Tunas Dwipa Matra. The method used is Simple Additive Weighting and Preference Selection Index Method to assist company management in assessing the best sales performance of employees in the company. Besides that, PT. Tunas Dwipa Matra strives to improve various service facilities that are friendly to consumers so that sales targets can be achieved every year. Based on the results of system testing at P.T Tunas Dwipa Matra, it can be concluded that the application made is as expected and can help the process of selecting the best salesperson. And the best sales in 2021 is Fitri with SAW value: 79 and PSI value: 0.832597